Intra-abdominal Hypertension and Abdominal Compartment Syndrome in patients undergoing emergency laparotomy - Madiha Fayyaz , Shahzad Haider , Abdul Hameed Khan , Sajid Nazir , Alina Hassan , Sajjad Hussain , Madiha Fayyaz , Shahzad Haider , Abdul Hameed Khan , Sajid Nazir , Alina Hassan , Sajjad Hussain (Journal of Rawalpindi Medical College, 2020)
Objective: The objectives of the Prospective observational study were to identify the frequency of abdominal compartment syndrome and intraabdominal hypertension in patients undergoing emergency laparotomy for trauma and peritonitis and to determine the impact of raised intraabdominal pressure on the overall morbidity and mortality. Materials and Methods: The study was conducted in the department of surgery Benazir Bhutto Hospital Rawalpindi. From June 2013 to May 2014 a total of 50 patients undergoing emergency laparotomy were included. IAP was measured preoperatively then postoperatively at 0, 6, 24 hours, and the findings were recorded on a specially designed preform. The patients having higher IAP were further evaluated up to 72 hours. All vitals, urine output, oxygen saturation, serum urea, creatinine were noted. The main outcomes were duration of hospital stay, the occurrence of burst abdomen, and mortality. Results: At the preoperative level the incidence of IAH was 86%. The mortality association with IAH at 6 hours postoperatively was quite significant (P<0.029). The incidence of postoperative ACS was 5% among the total patients and it was 15.6% in trauma patients. No significant association was found between IAP and occurrence of burst abdomen at any level (P values 0.4, 0.26, 0.53, 0.58 at intervals preoperatively, 0, 6, 24 hours postoperative respectively. Conclusion: Intraabdominal pressure is an important factor that predicts the mortality of patients undergoing emergency laparotomy. It should be carefully monitored and managed accordingly to avoid the detrimental effects on virtually all organ systems. Abdominal decompression in significantly elevated intraabdominal pressure reverts the physiological derangement of Intrabdominal hypertension.